Aggression in Down's syndrome. Issue 5 (September 2016) - Johnson, Racheal; Jarvaid, Amir; Narayran, Manoj; Michael, Dasari
Abstract : It has been speculated that there is a personality/behavioural phenotype among people with Down's syndrome, although research has been inconclusive. There is little evidence to support severe psychotic disturbance and aggressive behaviours being common in the Down's syndrome population. This case is that of a 24‐year‐old male with Down's syndrome who showed abnormally aggressive behaviours. He was kept in the community without psychiatric review, partly due to his behaviours being overlooked as he had a learning disability.